2016
DOI: 10.7146/math.scand.a-23295
|View full text |Cite
|
Sign up to set email alerts
|

On Vertex Decomposable Simplicial Complexes and Their Alexander Duals

Abstract: Abstract. In this paper we study the Alexander dual of a vertex decomposable simplicial complex. We define the concept of a vertex splittable ideal and show that a simplicial complex ∆ is vertex decomposable if and only if I ∆ ∨ is a vertex splittable ideal. Moreover, the properties of vertex splittable ideals are studied. As the main result, it is proved that any vertex splittable ideal has a Betti splitting and the graded Betti numbers of such ideals are explained with a recursive formula. As a corollary, re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(26 citation statements)
references
References 20 publications
1
25
0
Order By: Relevance
“…As a consequence of Theorem 3.3, we recover a result due to Moradi and Kosh-Ahang [17], proving that the Alexander dual of a vertex-decomposable simplicial complex admits a particular kind of splitting, the so-called x i -splitting (Corollary 4.3). In Corollary 4.5 we prove a Betti splitting result for shellable and constructible simplicial complexes, showing that in general they do not admit x i -splitting (Example 4.4).…”
Section: Introductionsupporting
confidence: 75%
See 1 more Smart Citation
“…As a consequence of Theorem 3.3, we recover a result due to Moradi and Kosh-Ahang [17], proving that the Alexander dual of a vertex-decomposable simplicial complex admits a particular kind of splitting, the so-called x i -splitting (Corollary 4.3). In Corollary 4.5 we prove a Betti splitting result for shellable and constructible simplicial complexes, showing that in general they do not admit x i -splitting (Example 4.4).…”
Section: Introductionsupporting
confidence: 75%
“…Many authors wrote papers applying the Eliahou-Kervaire technique to the resolution of special classes of monomial ideals (see e.g. [4], [5], [6], [8], [17], [19], [23], [24], [25]). Francisco, Hà and Van Tuyl proved in [7,Corollary 2.4] that if J and K have a linear resolution, then I = J + K is a Betti splitting of I.…”
Section: Introductionmentioning
confidence: 99%
“…Let i be the vertex in the definition of weakly vertex decomposable simplicial complex. Since del ∆ (i) is Cohen-Macaulay, then it is pure and i is a shedding vertex (see for instance [25] In the following example we show that the converse of the previous proposition does not hold, even in the Cohen-Macaulay case. Figure 3, due to Hachimori [18].…”
Section: The Recursive Formulamentioning
confidence: 70%
“…Moradi and Khosh-Ahang [20] defined the notion of vertex splittable ideal which is an algebraic analog of the vertex decomposability property of a simplicial complex and was defined as follows: Definition 1.1. A monomial ideal I in R is called vertex splittable if it can be obtained by the following recursive procedure:…”
Section: Preliminariesmentioning
confidence: 99%
“…Herzog, Hibi and Zheng [13] proved that the simplicial complex ∆ is shellable if and only if I ∨ has linear quotients. Recently Moradi and Khosh-Ahang [20] proved that the simplicial complex ∆ is vertex decomposable if and only if I ∨ is vertex splittable and also they showed that every vertex splittable ideal has linear quotients. Hence we have the following implications:…”
Section: Introductionmentioning
confidence: 99%